Molecular mechanism of ultrafast transport by plasma membrane Ca2+-ATPases - Deivanayagabarathy Vinayagam; Oleg Sitsel; Uwe Schulte; Cristina E. Constantin; Wout Oosterheert; Daniel Prumbaum; Gerd Zolles; Bernd Fakler; Stefan Raunser (Nature, 2025)
Abstract Tight control of intracellular Ca2+ levels is fundamental as they are used to control numerous signal transduction pathways1. Plasma membrane Ca2+-ATPases (PMCAs) have a crucial role in this process by extruding Ca2+ against a steep concentration gradient from the cytosol to the extracellular space2. Although new details of PMCA biology are constantly being uncovered, the structural basis of the most distinguishing features of these pumps, namely, transport rates in the kilohertz range and regulation of activity by the plasma membrane phospholipid PtdIns(4,5)P2, has so far remained elusive. Here we present the structures of mouse PMCA2 in the presence and absence of its accessory subunit neuroplastin in eight different stages of its transport cycle. Combined with whole-cell recordings that accurately track PMCA-mediated Ca2+ extrusion in intact cells, these structures enable us to establish the first comprehensive transport model for a PMCA, reveal the role of disease-causing mutations and uncover the structural underpinnings of regulatory PMCA–phospholipid interaction. The transport cycle-dependent dynamics of PtdIns(4,5)P2 are fundamental for its role as a ‘latch’ promoting the fast release of Ca2+ and opening a passageway for counter-ions. These actions are required for maintaining the ultra-fast transport cycle. Moreover, we identify the PtdIns(4,5)P2-binding site as an unanticipated target for drug-mediated manipulation of intracellular Ca2+ levels. Our work provides detailed structural insights into the uniquely fast operation of native PMCA-type Ca2+ pumps and its control by membrane lipids and drugs.